Potassium channel expression and function in the N9 murine microglial cell line - Pan, Geng (The University of Edinburgh, 2012)
Microglia are immunocompetent cells in the central nervous system that have many similarities with macrophages of peripheral tissues. Their activation protects local cells from foreign microbial infection in the CNS. However, “over-activated“ microglia become a “Double-edged sword” which show neuronal toxicity and are implicated in a variety of neurodegenerative diseases. Previous studies have suggested that potassium channels play a role in regulating microglial activation, migration and proliferation. However what kinds of potassium channel subunits are expressed in microglia, whether their expression changes after microglial activation and the functional role of most potassium channels expressed in microglia are still not fully characterized. To address these questions, we used the N9 mouse microglial cell line as a cell model for experiments in vitro. We first optimized the cell culture and lipopolysaccharide (LPS), the endotoxin of gram-negative bacteria, mediated stimulation of microglial activation that results in subsequent nitric oxide (NO) release. Using qRT-PCR, we analyzed mRNA expression of >80 potassium channel pore-forming subunits and their regulatory subunits in both LPS-treated (1μg/ml, 24hr) and untreated microglia. The subunits which displayed the highest mRNA expression in resting N9 cells included Kcnma1 (KCa1.1), Kcnk6 (K2p6.1), Kcnc3 (Kv3.3) and Abcc8 (SUR1). In addition, N9 cells also expressed the mRNAs for other channel subunits previously reported in microglia such as Kcnn4 (KCa3.1), Kcna3 (Kv1.3) and Kcna5 (Kv1.5) subunits. Of these channel subunits LPS had no significant effect on mRNA expression except for Kcnk6 which was significantly reduced. We then examined whether pharmacological manipulation of these channels controlled LPS-induced NO release. It was found out that the KCa3.1 selective blocker Tram34 and the Kv1.5 inhibitor propafenone (PPF) significantly decreased LPS-induced NO in agreement with data in primary microglia. Ba2+ that inhibits inwardly rectifying potassium channels as well as K2p6.1 also significantly attenuated LPS-induced microglial activation. Inhibition or activation of KCa1.1 channels by paxilline and NS1619 respectively had no significant effect. However, paxilline significantly attenuated the effect of Tram34, PPF and Ba2+ to control LPSinduced NO release while NS1619 significantly facilitated the effect of Tram34 and PPF. To investigate the major ionic currents expressed in N9 microglia with and without LPS application, we examined whole-cell ionic currents using the patch-clamp technique. Resting N9 cells display a small outward current at positive potentials but a large inwardly rectifying component at negative potentials in physiological potassium gradients. The outward current was dramatically increased by LPS application that was dependent upon the intracellular free calcium concentration. Paxilline or Tram34 was then applied to acutely block this apparent outward KCa current. The result indicated that the LPS triggered KCa current was mainly paxilline sensitive supporting a role for an LPS-induced increase in KCa1.1 channel current. In addition, by using current clamp the mean resting membrane potential of N9 cells was -50.6±6.6mV (N=7) determined in the presence of 1μM [Ca2+]i and -59.4±8.5mV (N=10) with 10nM [Ca2+]i. N9 cells did not display any spontaneous action potentials and the resting membrane potential was not significantly affected by LPS. To conclude, the work presented in this thesis extends the current knowledge regarding potassium channel mRNA expression in microglia and their function in microglial NO release. What is more, it was found that KCa1.1 current expression was increased in LPS-activated N9 cells and revealed KCa1.1 channels as a modulator of NO release by activated microglia.
Keywords: microglia; potassium channel